Placemaking as Public Space Planning Tool in New Providence, Bahamas - Pratt, Nastassia (IYARIC, 2024)
My research critically investigated the emergence of tourism development as a strategy in The Bahamas, the instrumentalization of the industry for planning public space, and the potential for “everyday placemaking” to be a touchstone for public space planning in the nation and the wider Caribbean region. In addition to a literature review and discussion, I conducted interviews, and an observational public space study of the Potter’s Cay Commercial Area from which these watercolours emerged.